Pleomorphic xanthoastrocytoma: Long-term results of surgical treatment and analysis of prognostic factors. (December 2013) - Gallo, Pasquale; Cecchi, Paolo Cipriano; Locatelli, Francesca; Rizzo, Paolo; Ghimenton, Claudio; Gerosa, Massimo; Pinna, Giampietro
Abstract Background. Pleomorphic Xanthoastrocytoma (PXA) is a rare brain tumour, most commonly affecting children and young adults. To date, only few data regarding the long-term follow-up of these patients after surgery are available. The aim of this study is to describe our single-institution experience in the surgical management of this particular glioma over a period of over 18 years. Methods. We performed a retrospective review of all cases of PXA (40 patients) operated upon at the Department of Neurosurgery of Verona, Italy, between 1990 and 2008. The impact of clinical, radiological, surgical and histological factors on overall survival (OS) and progression-free survival (PFS) was analysed by means of univariate and multivariate models. Findings. We achieved a gross total resection (GTR) in 65% of patients. Histological diagnosis was of grade II in 80%; anaplastic features were present in the remaining 20%. Adjuvant treatment, radiotherapy or chemo-radiotherapy, was administered in 40% of the cases. Median follow-up was 74 months. OS at 5- and 10 years was 76.32% and 68.24%, respectively. PFS at 5- and 10 years was 71% and 58%, respectively. In the multivariate model, histological grade, extent of resection and age at diagnosis (≤ 30 years vs > 30 years) were the only independent prognostic factors for both OS and PFS. Conclusions. Our retrospective long-term study confirms the relatively favourable prognosis associated with PXA. Young patients with a low-grade tumour (WHO grade II) who underwent GTR carry the longest OS and PFS.